Rotation Periods of Candidate Single Late-M Dwarfs in TESS - Samantha Lambier; Stanimir Metchev; Paulo Miles-Páez; Leslie Moranta; Dakota Wolfe; Joelene Hales; Jeffrey Martinovic (The Astronomical Journal)
Recent studies suggest that the angular momentum evolution of late-M and brown dwarfs differs from the well-known spin-down evolution of hotter stars. Characterizing the distribution of rotation periods of these objects in the solar neighborhood can help elucidate this evolutionary pathway just above, at, and below the hydrogen-burning limit. In this paper, we examine 399 candidate single late-M dwarfs with G  −  G _RP ≥ 1.4 mag (≳M6) using Transiting Exoplanet Survey Satellite (TESS) light curves. To determine rotation periods, we employed Lomb–Scargle periodograms to provide a first estimate of the period, then refined them with a Gaussian process approach, requiring multisector confirmation when available. We found 133 rotation periods, ranging from 2 hr to 6 days, and amplitudes between 0.08% and 2.71%. We find that the observed variability fraction in late-M dwarfs rises with the number of available TESS sectors, approaching an apparent ceiling of ∼50%. This likely reflects a detection limit determined by viewing geometry and supports the idea that spot-induced variability is common across the late-M and brown dwarf population. In our comparison with previously published late-M dwarf rotation periods reported, we found consistent results, confirming or updating 31 periods. Our findings expand the number of previously known late-M dwarf periods under 1 day by 76%. Combined with published rotation periods for a broader range of spectral types, we find a lower envelope on the rotation period decreasing from 5 hr at early-M dwarfs to 1 hr at L, T, and Y dwarfs.